Political ecology of forest carbon credit in Sarawak, Malaysia - Koh, Jane Sin Ai (2023)
The production of carbon credits using the carbon sequestration function of forests has been implemented successfully as revenue-generating projects around the world, but not in Sarawak, even though 62% of its terrestrial area is covered by forests. A lack of experience and understanding may result in failure to implement optimal policies that attract investment into forest carbon credit projects, therefore missing the opportunity to bring benefits to communities and generate revenue from forests while fulfilling international commitments regarding climate change and nature conservation. The objective of this study is to investigate how Sarawak can benefit from the production of forest carbon credits, and how this potential new industry can be optimally shaped, encouraged and governed. This research is an exploratory qualitative case study using an actor-oriented political ecology framework with the theory of access. Theories and prerequisites for payment for ecosystem services (PES) are used in the exposition of forest carbon credits as a tradable commodity. With this conceptual framework, the implications of forest carbon credit production can be understood against the socio-economic, political and cultural backdrop of Sarawak. Primary data was collected from interviews, focus groups, business reports and policy papers. The Sarawak State Legislative Assembly recently passed bills legislating carbon sequestration licences and carbon rights. Currently, carbon credits can be produced using industry standards and sold in global voluntary markets. Meanwhile, federal ministries are planning for a domestic voluntary carbon market, emissions trading scheme and forest conservation instruments. These future changes could affect market access and the price of carbon credits. This research found that the involvement of multiple federal and state ministries could lead to misalignment as they consider economic development, social welfare and international commitment aspects of forest carbon credits. Investors are motivated by profit and sustainability ratings. Their critical success factors include secure rights to carbon, land tenure that fulfils additionality, permanence and anti-leakage criteria, favourable licensing terms, clarity of future policy direction, knowledge of market and local circumstances, capital and community buy-in. Local communities may be impacted negatively if their access to forest is denied. They could be impacted positively if synergies are created with project proponents via co-benefit programmes. Communities with land rights could potentially use their land to produce carbon credits using land consolidation schemes. The detailed findings of this research are summarised as a transferable framework showing how elements of forest carbon credit production are impacting, and influenced by government, business and community actors. It also consists of multi-step access analyses on how each actor can access the benefits of forest carbon credits, and how they can be used to achieve other benefits. These findings are significant because they can guide policy-makers to consider all relevant aspects when formulating policies for the development and governance of forest carbon credit production, including those concerning communities. Potential investors could use these to guide their investment decisions. In conclusion, forest carbon credit production represents an opportunity with benefits that can be accessed by multiple stakeholders in Sarawak, if properly managed.